Artificial Unity in Scandal Mentality - Câmara, Clara; Roxo da Silva, Marco Antonio (Brazilian journalism research, 2020)
In this article we reflect on some of the narrative strategies used to structure political scandals. In order to do this we conceive political scandals in journalism as a mentality. The narrative strategies contained in this mentality help toward understanding these events, which we perceive as scandals. We shall present three of these strategies contained in what we call “artificial unity”, which transmit to readers the idea that there is endless and uniform narratives on scandals. Using both critical analysis of narrative and the indiciary paradigm, we focus our reflections on a number of scandals which occurred while the Workers’ Party (PT) government was in power, as they were reported in the O Globo newspaper. Neste artigo, propomos refletir sobre algumas das estratégias narrativas que estruturam a ideia de escândalo político. Para isso, propomos conceber os escândalos políticos, no jornalismo, como uma mentalidade. É essa mentalidade que resguarda estratégias narrativas que auxiliam na compreensão desses acontecimentos, que são concebidos como escândalos. Aqui, focamos em apresentar três dessas estratégias, contidas no que chamamos de “unidade artificial”, e que oferecem ao leitor uma ideia de que há uma grande narrativa de escândalo, uniforme e infindável. Unindo pressupostos da Análise crítica de narrativa e do paradigma indiciário, focamos nossas reflexões na listagem de escândalos dos governos do Partido dos Trabalhadores (PT), feita pelo jornal O Globo. En este artículo, proponemos reflexionar sobre algunas de las estrategias narrativas que estructuran la idea del escándalo político. Para eso, proponemos concebir los escándalos políticos, en el periodismo, como una mentalidad. Es esta mentalidad la que protege las estrategias narrativas que ayudan a comprender estos eventos, que se conciben como escándalos. Aquí, nos enfocamos en presentar tres de estas estrategias, contenidas en lo que llamamos "unidad artificial", y que ofrecen al lector una idea de que hay una gran narrativa de escándalo, uniforme e interminable. Uniendo los supuestos del análisis crítico de la narrativa y el paradigma indicativo, centramos nuestras reflexiones en la lista de escándalos de los gobiernos del Partido de los Trabajadores (PT), realizada por el periódico O Globo.